2017
DOI: 10.1186/s13071-017-2533-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic monitoring of Schistosoma mansoni in Tanzanian schoolchildren five years into a preventative chemotherapy national control programme

Abstract: Background Schistosoma mansoni is a parasite of profound medical importance. Current control focusses on mass praziquantel (PZQ) treatment of populations in endemic areas, termed Preventative Chemotherapy (PC). Large-scale PC programmes exert prolonged selection pressures on parasites with the potential for, direct and/or indirect, emergence of drug resistance. Molecular methods can help monitor genetic changes of schistosome populations over time and in response to drug treatment, as well as estimate adult wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 32 publications
4
40
0
Order By: Relevance
“…Although this could potentially reflect species differences between S. haematobium and S. mansoni , consistent with their contrasting mean daily egg output per adult worm, it is important to acknowledge that the aforementioned Tanzanian S. mansoni populations represented a true pretreatment baseline population, 44 whereas these Zanzibar S. haematobium populations had been subjected to many previous treatments, over several years, with PZQ before the start of the SCORE/ZEST program. 62 Indeed, within these Zanzibarian S. haematobium populations, there was evidence of density dependence within individuals in relation to host age and gender (and, hence, also infection intensity profiles), consistent with that previously documented through population genetic analyses for both S. mansoni in Tanzania 31 , 47 and S. haematobium in Mali. 44 Furthermore, population genetic and statistical analyses did indicate inherent differences in schistosome fecundity levels by site across both islands, frequently consistent with those shehias that went on to be classed as nonresponder hotspot sites.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although this could potentially reflect species differences between S. haematobium and S. mansoni , consistent with their contrasting mean daily egg output per adult worm, it is important to acknowledge that the aforementioned Tanzanian S. mansoni populations represented a true pretreatment baseline population, 44 whereas these Zanzibar S. haematobium populations had been subjected to many previous treatments, over several years, with PZQ before the start of the SCORE/ZEST program. 62 Indeed, within these Zanzibarian S. haematobium populations, there was evidence of density dependence within individuals in relation to host age and gender (and, hence, also infection intensity profiles), consistent with that previously documented through population genetic analyses for both S. mansoni in Tanzania 31 , 47 and S. haematobium in Mali. 44 Furthermore, population genetic and statistical analyses did indicate inherent differences in schistosome fecundity levels by site across both islands, frequently consistent with those shehias that went on to be classed as nonresponder hotspot sites.…”
Section: Introductionsupporting
confidence: 86%
“…One recent population genetic study, however, estimated the number of adult worm genotypes of S. mansoni in Tanzanian children using parentage analysis and sibship reconstruction from microsatellite analyses of miracidia. 47 Analyses using our newly developed statistical tools indicated that, despite the (minimum) number of adult worm pairs present in school-aged children having reduced over time in response to PZQ treatment, there was little or no evidence of any corresponding reduction in parasite infection intensities, as measured by EPG. This indicated there was a relaxation of the density-dependent inhibition on schistosome fecundity following treatment with PZQ among these S. mansoni populations.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Praziquantel (PZQ), a drug co-developed by Bayer AG and Merck KGaA in the 1970s, has been implemented in many national programs as an integral component of control and elimination strategies and is the drug of choice for the treatment of schistosomiasis (Olveda et al, 2016;Bergquist et al, 2017;Gower et al, 2017;Kabore et al, 2017;Kimani et al, 2018). Although PZQ is considered non-toxic and highly effective against adult schistosomes, it is unable to kill developing schistosomes and the individual remains susceptible to subsequent infections.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different pairings may result in different fecundity rates. This poses significant challenges, but molecular approaches such as parentage and/or sib‐ship analysis of schistosome eggs present opportunities to improve assumptions regarding association between egg output and number of worm pairs in an individual (Lu et al., ; Gower, Gehre, Marques, Lwambo, & Webster, ).…”
Section: Considerations For Developing and Parameterizing A Transmissmentioning
confidence: 99%